2019
DOI: 10.1029/2019jd030387
|View full text |Cite
|
Sign up to set email alerts
|

Global 3‐D Simulations of the Triple Oxygen Isotope Signature Δ17O in Atmospheric CO2

Abstract: The triple oxygen isotope signature Δ17O in atmospheric CO2, also known as its “17O excess,” has been proposed as a tracer for gross primary production (the gross uptake of CO2 by vegetation through photosynthesis). We present the first global 3‐D model simulations for Δ17O in atmospheric CO2 together with a detailed model description and sensitivity analyses. In our 3‐D model framework we include the stratospheric source of Δ17O in CO2 and the surface sinks from vegetation, soils, ocean, biomass burning, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(87 citation statements)
references
References 124 publications
(247 reference statements)
2
82
3
Order By: Relevance
“…However, the inter-hemispheric difference of Δ 17 O in meteoric water is not large (Elkins et al, 1996) and CO 2 equilibrates rapidly with the meteoric water. Therefore, we do not expect large difference in the Δ 17 O values of CO 2 from the northern hemisphere and southern hemisphere (also see Koren et al, 2019). Hoag et al (2005) also showed that despite a difference between the two hemispheres in fluxes of ocean sink and source and leaf/soil exchange, the model difference is only about 0.01 ‰.…”
Section: Earth and Space Sciencementioning
confidence: 80%
See 1 more Smart Citation
“…However, the inter-hemispheric difference of Δ 17 O in meteoric water is not large (Elkins et al, 1996) and CO 2 equilibrates rapidly with the meteoric water. Therefore, we do not expect large difference in the Δ 17 O values of CO 2 from the northern hemisphere and southern hemisphere (also see Koren et al, 2019). Hoag et al (2005) also showed that despite a difference between the two hemispheres in fluxes of ocean sink and source and leaf/soil exchange, the model difference is only about 0.01 ‰.…”
Section: Earth and Space Sciencementioning
confidence: 80%
“…This anomalous CO 2 can be transported from the stratosphere to the troposphere by the large scale Brewer-Dobson circulation and synoptic eddy diffusion. The mixing of this downwelling CO 2 with near normal lower level CO 2 may change the isotopic anomaly in the latter, providing an opportunity for determining CO 2 fluxes associated with biogeochemical cycles (Hoag et al, 2005;Koren et al, 2019;Liang, Mahata, Laskar, Thiemens, et al, 2017;Liang, Mahata, Laskar, & Bhattacharya, 2017;Young et al, 2014). A detectable level of anomaly and anomaly gradient would exist in the middle and lower troposphere if the rates of mass dependent surface processes are not fast enough to erase the signature from the stratosphere.…”
Section: Introductionmentioning
confidence: 99%
“…Figure S13. A 3D model result for the seasonal cycle of the globalΔ 17 O value of leaf water for the year 2012 (Koren et al, 2019). Note that Δ 17 O value is reported here with l value of 0.5229.…”
Section: Derivation Of the 18 O-photosynthetic Discriminationmentioning
confidence: 99%
“…Figure S14 Annual variability of ci/ca ratio for C4 and C3 plants from SiBCASA model (Schaefer et al, 2008;Koren et al, 2019). Table S1 Reproducibility of the extraction system and the CO2-O2 exchange system.…”
Section: Derivation Of the 18 O-photosynthetic Discriminationmentioning
confidence: 99%
“…The 17 O-excess of CO2 (Δ 17 O, involving the triple oxygen isotope composition of CO2, see equation 5) has been suggested as additional independent tracer for constraining global GPP (Hoag et al, 2005;Thiemens et al, 2013;Hofmann et al, 2017;Liang et al, 2017b;Koren et al, 2019). Because Δ 17 O is not or only slightly sensitive to mass-dependent fractionation processes acting on CO2 and H2O, its interpretation may be less sensitive to the effects mentioned above.…”
Section: Introductionmentioning
confidence: 99%